Liquidation and its effect on construction trade creditors in New Zealand - Ramachandra, T; Rotimi, J.O.B. (Emerald, 2012)
Purpose – The construction industry suffers from significantly large number of insolvencies than other industries due to its inherent characteristics and these have dire consequences on project participants and the industry at large. The purpose of this paper is to determine both the causes of liquidation and the distribution of losses to construction parties through an analysis of liquidators' reports on some construction firms based in New Zealand. Design/methodology/approach – The study collates primary information from Liquidators' reports for firms operating within three main sub-sectors of the construction industry. The information was then analysed using simple interpretative techniques for the period covering 2005 to 2009. Altogether the data set used for the analyses included 65 construction firms. Findings – The major reasons for construction insolvencies are found to be: financial difficulties due to non-payment, poor debt management, drop in property prices, and the liquidation of related companies. Other reasons are discussed within the paper. The paper also illustrates that liquidation of construction firms causes payment delays and consequential losses to project stakeholders. The results show that settlements of trade creditors take an average of 18 months and payment is usually not received fully after liquidation proceedings. It is apparent that there is little security for payment losses in construction insolvencies. Originality/value – In this paper, information on reasons for and the consequences of liquidation provide a valuable thought-starter for managing payment problems in the construction industry. The paper extends knowledge on possible security to payment losses experienced by lower tier project participants when the upper tiers become illiquid.
Keywords: Construction industry; Creditors; Insolvency; Liquidation; New Zealand; Payment delays; Payment losses; Trade creditors; Construction industry; Creditors; Insolvency; Liquidation; New Zealand; Payment delays; Payment losses; Trade creditors